2005
DOI: 10.1007/s00348-005-0927-2
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy effects on flow transition in low-density inertial gas jets

Abstract: Effects of buoyancy on transition from laminar to turbulent flow are presented for momentum-dominated helium jet injected into ambient air. The buoyancy was varied in a 2.2-sec drop tower facility without affecting the remaining operating parameters. The jet flow in Earth gravity and microgravity was visualized using the rainbow schlieren deflectometry apparatus. Results show significant changes in the flow structure and transition behavior in the absence of buoyancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Although the transition Re is about a factor of 4 lower than the typical transition value (Re ∼ 1 760 for flow inside a cylindrical pipe, i.e., Poiseuille flow25), our Reynolds number is consistent with other reports (Re ∼ a few hundred) for the flow transition of helium plasma jet in open air 26, 27. This low Reynolds number flow transition was observed and explained in helium gas jets by the buoyancy effect 27–29. According to these reports, the buoyancy effect may be significant for flow transition in the low momentum and momentum dominated helium jet.…”
Section: Resultssupporting
confidence: 90%
“…Although the transition Re is about a factor of 4 lower than the typical transition value (Re ∼ 1 760 for flow inside a cylindrical pipe, i.e., Poiseuille flow25), our Reynolds number is consistent with other reports (Re ∼ a few hundred) for the flow transition of helium plasma jet in open air 26, 27. This low Reynolds number flow transition was observed and explained in helium gas jets by the buoyancy effect 27–29. According to these reports, the buoyancy effect may be significant for flow transition in the low momentum and momentum dominated helium jet.…”
Section: Resultssupporting
confidence: 90%
“…It reaches a maximum at a Reynolds number of roughly 1500 and decreases afterwards [5]. Buoyancy has been found to play a key role in the flow transition from laminar to turbulent flow in the case of helium jets [13,14]. This effect has been observed for Richardson numbers between 3.53 × 10 −3 and 19 × 10 −3 [13].…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, cold laminar gas jets (e.g., at room temperature) can only maintain their laminar flow state within a short distance from the exit of the jet nozzle (usually, the jet laminar-region length/diameter ratio does not exceed 10) even at comparatively low Reynolds numbers [1,2]. Linear instability analysis [3] and experimental observation [2] showed that the cold laminar gas jet becomes even more unstable when the density of the gas jet is less than that of the ambient gas.…”
Section: Introductionmentioning
confidence: 99%
“…Linear instability analysis [3] and experimental observation [2] showed that the cold laminar gas jet becomes even more unstable when the density of the gas jet is less than that of the ambient gas. Since the density of a plasma jet is always much less than that of the cold ambient air, one might anticipate that it is hard to generate a stable long laminar plasma jet in atmospheric-pressure air surroundings.…”
Section: Introductionmentioning
confidence: 99%